Elucidating the clinker-based catalyst deactivation for biodiesel production in a continuous microwave-assisted reactor - Gimbun, Jolius; Mohd Affandi, Mohd Ali; Cheng, Cheng Kui; Sumaiya, Zainal Abidin; Maizirwan, Mel; Chin, Siew Choo (Elsevier Ltd, 2025)
A clinker-based catalyst (CBC) was synthesized by incipient wetness impregnation with potassium hydroxide (10 wt%), then calcined at 700 ◦C. XRD and EDX analyses revealed that CaO (66.61 wt%) and Ca (34.63 wt%) are the primary constituents of the CBC, with the main crystalline phases identified as Ca2Al0.67Mn0.33FeO5 (monoclinic) and Ca3SiO5 (orthorhombic). This catalyst was effectively employed for the transesterification of waste cooking oil (WCO) in a continuous microwave-assisted reactor (CMAR), achieving a fatty acid methyl ester (FAME) yield of over 92.8 % under optimal conditions: a methanol to oil molar ratio of 12:1, a catalyst concentration of 5 wt% (catalyst/oil), and a reaction temperature of 65 ◦C. Moisture in CBC can reduce its performance by over 36 %. The catalyst was recovered and reused four times with minimal loss of activity. Analysis of the reused catalyst indicated that the reduction in catalytic performance was due to leaching, catalyst poisoning, and a decrease in surface area and porosity. Due to its reusability, the clinker-based catalyst has the potential to replace homogeneous catalysts, thereby reducing biodiesel production costs.